Cardiac Dysrhythmias With Midazolam Sedation - Rodrigo, Chandra R. (1990)
A randomized cross-over study was made of 32 young healthy Hong Kong Chinese to compare the incidence and nature of dysrhythmias that occurred during third molar surgery done under local anesthesia, alone or supplemented with midazolam sedation. The incidence of dysrhythmias during surgery was not significantly different during the two procedures. However prior to surgery, 25% of the patients had dysrhythmias during sedation with midazolam. The majority of dysrhythmias were infrequent unifocal ventricular ectopics. During sedation with midazolam it may be beneficial to monitor the electrocardiogram, especially in high risk patients such as those suffering from ischaemic heart disease, cardiomyopathy, and those on antidysrhythmic drugs.